Affixoids: Evidence from Persian - mehdi sabzevari; Shadi Davari (زبان پژوهی)
Some evidence from Persian supports the existence of constituents that show properties of affixoids or what might be referred to as semi-affixes. These constitutes can stand independently but, in combination with certain nouns, show a rather notable distribution and, in that context, behave like a derivational affix. In such contexts, there is a semantic change in the derived form when an affixoid is added to a base. Regarding the frequency of affixoids in Persian, it is observed that their usage is also very frequent in sentences and phrases as independent words. There are several affixoids attested in Persian but only a few will be discussed here as representative examples. It can be argued that affixoids hold an independent status in linguistic literature as a semi-category. In this paper, some affixoids from Persian will be discussed as they might be prefixoids or suffixoids. All examples are from spoken and written Persian.